This preview shows page 1. Sign up to view the full content.
Unformatted text preview: en ( -6,10 ) . We can verify this
by evaluating the function at x = -6 . If we are correct we should get a value of 10. Let’s verify
this. f ( -6 ) = 2 ( -6 + 3) - 8 = 2 ( -3) - 8 = 2 ( 9 ) - 8 = 10
2 2 So, we were correct. Note that we usually don’t bother with the verification of this point.
Okay, it’s time to sketch the graph of the parabola. Here it is. Note that we included the axis of symmetry in this graph and typically we won’t. It was just
included here since we were discussing it earlier.
[Return to Problems] (b) g ( x ) = - ( x - 2 ) - 1
2 Okay with this one we won’t put in quite a much detail. First let’s notice that a = -1 which is
negative and so we know that this parabola will open downward.
Next, by comparing our function to the general form we see that the vertex of this parabola is
( 2, -1) . Again, be careful to get the signs correct here!
Now let’s get the y-intercept. g ( 0 ) = - ( 0 - 2 ) - 1 = - ( -2 ) - 1 = -4 - 1 = -5
2 2 The y-intercept is then ( 0, -5 ) .
Now, we know that the vertex starts out below the x-axis and the parabola opens down. This
View Full Document
- Spring '12